Equivalent strain, microstructure and hardness of H62 brass deformed by constrained groove pressing - Peng, Kaiping; Mou, Xueping; Zeng, Jiawei; Shaw, Leon L.; Qian, K.-W. (Computational materials science, 2011)
▸ Fully constrained CGP results in 40% more strains than partially constrained CGP. ▸ Fully constrained CGP has different strain distribution from partially constrained CGP. ▸ Non-uniform strain during CGP results in non-uniform microstructure and hardness. Constrained groove pressing (CGP) has been developed to refine grain sizes, and in most cases is conducted under partially constrained conditions. Here we report the first investigation of the Von Mises equivalent strain and its distribution in samples subject to CGP under partially constrained conditions. Using finite element modeling, we show that the value of the equivalent strain and its distribution depend strongly on the constraint condition of CGP. Experiments using an annealed H62 brass confirm the simulation and reveal that the non-uniform strain distribution results in the corresponding non-uniform profile of the grain size and hardness. These findings are of great importance since many CGP are conducted under partially constrained conditions which generate lower equivalent strains than the counterpart under fully constrained conditions.